Estimates of intense noise for inhomogeneous diffusion processes - Maiboroda, R. E. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
Nonparametric estimates of noise intensityg(t) are obtained. These estimates are constructed for datax(t) defined by the equationdx(t)=f(x(t),t)dt+g(t)dw(t). The validity of the estimates is proved.